THE REPRESENTATION OF THE ISLAMIC VEIL IN INDONESIAN CONTEMPORARY ART: A FEMINIST POSTSTRUCTURALIST APPROACH - Rosmah Tami (Elite : English and Literature Journal, 2013)
AbstractVeiling in Indonesia is a unique phenomenon. Once it was banned in the public arena and has a negative menaing, yet several uears later its meaning was changed into more positive meanings. this article explores a poen published in the transition era when the meaning of the veil had been undergoing some changes. Syair LautanaJilbab is written by MH Ainun Najib, a most famous religious leader in Indonesia. This article shows how poemproduced new meaning dispalyed by the poem, and how people respond to the new meanings. The veil new meanings have influenced large people to adopt veiling as a religious symbol of their spiritual awareness.